Implementasi pembelajaran berdiferensiasi pelajaran matematika metode PBL (Problem Based Learning) dengan media worksheet - Faizatun, Dwita; Sasomo, Budi (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2024)
Differentiated learning in this research aims to increase interest and enthusiasm in learning mathematics with the help of worksheets. The use of differentiation learning strategies aims to provide activities that suit students' initial needs or abilities so that learning needs can be met. Mathematics is often considered difficult and confusing for students. In research regarding the implementation of PBL using worksheet media in Class VII Mathematics at SMPN 2 Bringin Ngawi, qualitative descriptive methods were used through observation, interviews with teachers, and documentation. Data analysis was carried out using a thematic approach developed by Huberman and Miles to understand how PBL was implemented and its impact on students' understanding and skills. The results of this research are that the implementation of Problem Based Learning (PBL) at SMPN 2 Bringin Ngawi increases students' active participation and collaboration abilities, supported by the use of technology, and increases their problem solving abilities and motivation.